Modyul sa retorika : masining na pagpapahayag - De Dios, Luz A. (Pateros, Metro Manila, 2012)
Includes bibliography
Keywords: Filipino language -- Rhetoric; Filipino language -- Study and teaching (higher).; Filipino language -- Composition and exercise